The role of alphabet book in improving preschool children’s letter recognition - Nurbaeti Syam; Ahmad Afiif; Eka Damayanti (Journal of Early Childhood Care and Education (JECCE), 2022)
Letter recognition is the first stage in developing children’s reading skills. It is hence important to optimize the stimulus for letter recognition, either in terms of methods or media. One of the media helpful for improving children’s letter recognition is the alphabet book. The present study aims to depict the role of the alphabet book in improving preschool children's letter recognition. This qualitative library research garnered articles and books using two keywords: alphabet book and letter recognition. The data were collected using documentation and analyzed using Miles and Huberman’s descriptive analysis. The result showed that Alphabet Book improved children’s letter recognition. Alphabet book could improve children’s ability to recognize letter shapes and sounds and write the letter. This improvement appears to be accounted for by the book’s various themes, attractive illustrations, and words representing each letter. The alphabet book is also interesting when used together with storytelling and play methods. Alphabet book also plays a role in improving children's learning interest and enriching their vocabulary.